Rivaroxaban for the treatment of cerebral venous thrombosis - Sara Esmaeili; Meysam Abolmaali; Sobhan Aarabi; Mohammad Reza Motamed; Samira Chaibakhsh; Mohammad Taghi Joghataei; Mohammad Mojtahed; Zahra Mirzaasgari (BMC Neurology, 2021)
Abstract Background New Oral Anticoagulants (NOACs) such as Rivaroxaban are introduced as alternatives to conventional vitamin-K antagonists in the long-term treatment of thrombotic events due to their lower bleeding risk. There is a lack of evidence on the effectiveness and safety of Rivaroxaban in Cerebral venous thrombosis (CVT). This study aims to assess the effectiveness and bleeding risk of Rivaroxaban in comparison with Warfarin for the treatment of CVT. Materials and methods 36 patients with diagnosis of CVT were included. Clinical and background information was assessed on admission and patients were followed for at least 12 months. Measured outcomes were modified Rankin Scale (mRS), evidence of recanalization on contrast-enhanced Brain MR venography (MRV) and major or minor bleeding. Patients were divided into two groups according to the type of oral anticoagulant (Rivaroxaban vs Warfarin). Groups were compared in terms of final outcomes and side effects. Result Overall, 13 (36.11%) patients received Warfarin and 23 (63.89%) received Rivaroxaban. Optimal mRS score (0–1) was attained in 9 of 10 (90%) of patients treated with Rivaroxaban and 19 of 22 (86.36%) of patients received Warfarin. MRV showed complete or partial recanalization in 12 of 14 (85.71%) patients treated with Rivaroxaban and all patients in the Warfarin group. There was no significant difference between the two groups in terms of major and minor hemorrhage. Conclusion Rivaroxaban holds promise for the treatment of CVT.